Education and the social order - Russell, Bertrand (Routledge classics, 2010)
Bertrand Russell was renowned for his provocative views on education. Considered an educational innovator, Russell attempted to create the perfect learning institution. Despite the failure of this practical vision, it did not stop him from continuing to strive towards inventing and arguing for a system of education free from repression. In Education and the Social Order, Russell dissects the motives behind educational theory and practice, and in doing so lays out original and controversial arguments for the reformation of the education of the individual.